2014
DOI: 10.1016/j.immuni.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Myeloid Cells in SIV-Infected Primates Acquire Viral DNA through Phagocytosis of Infected T Cells

Abstract: Summary The viral accessory protein Vpx, expressed by certain simian and human immunodeficiency viruses (SIVs and HIVs), is thought to improve viral infectivity of myeloid cells. We infected 35 Asian macaques and African green monkeys with viruses that do or do not express Vpx, and examined viral targeting of cells in vivo. While lack of Vpx expression affected viral dynamics in vivo, with decreased viral loads and infection of CD4+ T cells, Vpx expression had no detectable effect on infectivity of myeloid cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
103
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 50 publications
15
103
0
1
Order By: Relevance
“…In agreement with our findings in macaques in vivo, the preferential infection of resident macrophages was recently described in human urethral tissue exposed ex vivo to HIV-1 (87). It was recently suggested that myeloid cells in the gut and lymphoid tissues from SIV-infected primates are resistant to infection and acquire SIV DNA primarily through the phagocytosis of infected T cells (90). However, it was reported that macrophages in lymph nodes and mucosal tissues get heavily infected in macaques depleted in CD4 ϩ T cells (91) and that the uptake of HIV-infected T lymphocytes by blood-derived macrophages leads to their infection (92).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings in macaques in vivo, the preferential infection of resident macrophages was recently described in human urethral tissue exposed ex vivo to HIV-1 (87). It was recently suggested that myeloid cells in the gut and lymphoid tissues from SIV-infected primates are resistant to infection and acquire SIV DNA primarily through the phagocytosis of infected T cells (90). However, it was reported that macrophages in lymph nodes and mucosal tissues get heavily infected in macaques depleted in CD4 ϩ T cells (91) and that the uptake of HIV-infected T lymphocytes by blood-derived macrophages leads to their infection (92).…”
Section: Discussionsupporting
confidence: 92%
“…7,35 Finally, it is noteworthy that myeloid cells (macrophages, monocytes, and dendritic cells) have been shown to become infected with HIV following phagocytosis of infected T cells in the SIV model of infection. 38 A limitation of our study is the small sample size and the limited number of clones analyzed per compartment. The challenges in amplifying the HIV genome from tissue restricted our use of limiting dilution techniques such as single genome amplification, which have been shown to mitigate the problem of variant resampling within quasispecies.…”
Section: Discussionmentioning
confidence: 99%
“…36 Second, the influx of activated immune cells including differentiated macrophages to the site of infection regardless of HIV status and the concomitant HIV-related T cell depletion 19 mean that an environment permissive to exploiting macrophages may be created in spinal TB granulomas. However, there remains controversy around this paradigm with conflicting reports showing that CD4 depletion either has an impact 37 or has no impact 38 on HIV infection of myeloid cells. Third, longlived HIV lineages have previously been correlated with macrophage-targeting HIV variants in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…It will be necessary to investigate cells other than CD4 + lymphocytes and tissues other than blood, especially the CNS. Also of note, the problem of measuring DNA in CD4 + lymphocytes is further compounded in macrophages, which may contain viral DNA and protein as a result of their phagocytic function, rather than their role in replication (86).…”
Section: Latency In Cells Other Than Cd4 + Lymphocytesmentioning
confidence: 99%